2021
DOI: 10.3390/horticulturae7050112
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Impacts of Temperature and Elevated CO2 on Basil (Ocimum basilicum L.) Root and Shoot Morphology and Growth

Abstract: Recent evidence suggests that the effects of temperature significantly affect the growth and development of basil plants with detrimental impacts on yield. The current research investigated the interactive effects of varying temperature and CO2 levels on the shoot and root morphology and growth of early and late-season basil plants. Basil plants were subjected to control (30/22 °C), low (20/12 °C), and high (38/30 °C) temperature under ambient (420 μL L−1) and elevated (720 μL L−1) CO2 concentrations. Decreasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Results observed in Arabidopsis thaliana leaves [ 64 ], soybean [ 65 ], cotton [ 25 ], maize [ 29 , 66 ]; Phaseolus vulgaris [ 67 ], sweet potato [ 68 ], and basil [ 69 ] further corroborated our results, such as a reduction in total leaf area and fresh and dry weights, number of leaves, and height of plants ( Table 3 ) under higher UV-B levels. In contrast to our results, Sakalauskaite et al [ 70 ] reported an increase in plant height, leaf area, and dry weight under elevated UV-B in Ocimum basilicum .…”
Section: Discussionsupporting
confidence: 84%
“…Results observed in Arabidopsis thaliana leaves [ 64 ], soybean [ 65 ], cotton [ 25 ], maize [ 29 , 66 ]; Phaseolus vulgaris [ 67 ], sweet potato [ 68 ], and basil [ 69 ] further corroborated our results, such as a reduction in total leaf area and fresh and dry weights, number of leaves, and height of plants ( Table 3 ) under higher UV-B levels. In contrast to our results, Sakalauskaite et al [ 70 ] reported an increase in plant height, leaf area, and dry weight under elevated UV-B in Ocimum basilicum .…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, the high-temperature stress was observed to increase the g s , E, C i , apparent quantum yield, maximum photosystem II efficiency, and finally, maximum P n of basil plants. This observation could be linked to the positive impacts of high-temperature treatments detected on the morphological parameters of basil plants [26]. Comparable results were accounted for by Chang et al [11].…”
Section: Discussionmentioning
confidence: 82%
“…Basil is renowned for its ability to thrive in diverse temperature ranges and geographical regions, making it a globally cultivated herb [ 14 ]. The genus Ocimum , which belongs to the Lamiaceae (Labiatae) family, has distribution throughout tropical and subtropical America, Africa, and Asia continents [ 15 ].…”
Section: Ocimum Basilicum L Ecology and Morphologymentioning
confidence: 99%